(untitled) (African Human Rights Yearbook / Annuaire Africain des Droits de l’Homme, 2022)
RÉSUMÉ: Bien qu’effective, la protection juridictionnelle régionale des droits de l’homme en Afrique connait un certain nombre de défis. Au rang de ses défis figure le verrou procédural de la déclaration facultative d’acceptation de la juridiction obligatoire de la Cour africaine des droits de l’homme et des peuples. Le présente article se propose de faire une analyse de ces déclarations depuis l’entrée en vigueur du Protocole de Ouagadougou jusqu’en fin 2017. Il se dégage de cette réflexion que les choix circonstanciels des États entraînent une mise en œuvre ambivalente des déclarations en ce que la clause de l’article 34(6) institue un système donc la mise en œuvre handicape l’envol de la juridiction africaine, d’une part, et d’autre part, que cette mise en œuvre timorée renforce plutôt les juridictions communautaires qui contribuent à pallier aux insuffisances du mécanisme continental de protection des droits de l’homme. TITLE AND ABSTRACT IN ENGLISH: The declaration under article 34(6) of the Ouagadougou Protocol in the African human rights system: between continental regression and regional progress ABSTRACT: Although effective, the regional jurisdictional protection of human rights in Africa faces a number of challenges. Among its challenges is the procedural lock of the optional declaration to accept the compulsory jurisdiction of the African Court on Human and Peoples’ Rights. This article analyses these declarations since the entry into force of the Ouagadougou Protocol until the end of 2017. Evidence from this reflection is the fact that the circumstantial choices of states involve an ambivalent implementation of the declaration in article 34(6) establishing a system and thereby making implementation difficult. On the one hand, this results in the avoidance the Court’s jurisdiction. On the other hand, the laxity in implementation strengthens the jurisdiction of subregional courts, which contributes to overcoming the shortcomings of the continental mechanism for the protection of human rights.